A Comparison of Corporate Governance Practices in State-owned Enterprises and Their Private Sector Peers in India. (July 2016) - Subramanian, S.
In India, Corporate governance norms were prepared with the assumption that firms were controlled by private players. However, in India, there are many firms that are majority-owned by the State or the government. Literature on corporate governance has highlighted the differences in the governance practices of government- and private-owned enterprises. But the parameters on the basis of which such differences emerge have not been studied. This article attempts to fill in the research gaps by analyzing the corporate governance practices of State-owned enterprises, known as public sector undertakings (PSUs), and family-owned enterprises in the Indian context by using the case study method. Five PSUs along with five family-owned private sector enterprises were selected for the study and their board practices were compared. The findings indicate significant differences in the board structure and the director's compensation structure of PSUs and family-owned firms. These findings suggest that policy-makers need to consider the State ownership issue separately while making corporate governance norms.